Technological Progress, Globalization, and Secular Stagnation - Milenko Popović (Journal of Central Banking Theory and Practice, 2018)
After the 2008 crisis, despite economic recovery that started in 2009, the world economy has experienced a downward shift of its growth path and a consequent decline. As shown at the beginning of this paper, this shift and growth rate stagnation are totally attributable to the economic dynamics in developed economies, the USA and the EU. Explanations of this phenomenon can be divided into two large groups: explanations that belong to the demand side and those that belong to the supply side. The aim of this paper is to give a critical survey of the most important explanations for the ongoing growth stagnation in developed countries and consequently in the entire world economy. This ongoing prolonged stagnation can only be explained by looking at both, the demand and supply sides of the explanation, and particularly by taking a closer look at the interaction between aggregate demand and aggregate supply. In other words, secular stagnation manifests itself as a problem of the limitation of long run growth of aggregate demand. However, in order to explain the causes of those demand limitations, we have to undertake a careful analysis of the supply side dynamics, especially the dynamics of innovations, which bring us to circular and cumulative causation. In order to explain the numerous consequences of this stagnation and to solve some important puzzles, like the productivity paradox for example, a special emphasis is given to the analysis of deindustrialization and the consequent strange reoccurrence of a dual economy within most developed countries during the period of the IT revolution and hyper-globalization. It will also be shown that this new dual economy presents serious limitations for further technological advancement and economic development, quite contrary to the old dualism which contributed to an acceleration of economic growth.
Keywords: O30; O40; E30; 330; Secular stagnation; Economic growth; Dual economy; Technological progress; Globalization; Inequalities